(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In this article we take into consideration the integrative mechanisms of influence on the forming the learners artistic skills. We can differentiate the following aspects stimulation of folk dancing art such as. The spiritual-integral attitude to the achievements of the traditional national culture, the understanding of the symbols, the realization of the emotionally figurative content of the Ukrainian people’s myth poetical creation.